Right to defense violated due to lack of time to respond to request for approval - Secaira Vaca , Gabriel Alejandro (2025)
This study analyzes the violation of the respondent’s right to defense in the administrative prior approval (visto bueno) procedure in Ecuador, caused by the insufficient time granted to respond to the petition. Using a qualitative approach and exegetical and hermeneutic methods, the Ecuadorian legal framework (Labor Code and Ministerial Agreements MDT-2024-041 and MDT-2025-043) was examined and compared with international legislation (Peru, Colombia, and Chile). The findings show that the current two-day deadline is incompatible with Article 76, paragraph 7, letter b) of the Constitution, which guarantees adequate time and means for a fair and technical defense. This situation worsens when immediate suspension of the employment relationship is requested, depriving the worker of access to their workplace and documentation. The legal comparison revealed that Ecuador is the only country among those analyzed with a response period shorter than five days. As a result, it is proposed to amend Article 621 of the Labor Code and Article 10 of Ministerial Agreement MDT-2024-041, extending the response period to five business days, thereby balancing procedural speed with due process.